Documenta X - the book. (Stuttgart : Cantz, 1997)
Acconci, Vito ; Adams, Robert ; Althamer, Pawel ; Andre, Carl ; Archigram ; Archizoom Association ; Art & Language ; Artaud, Antonin ; Aya & Gal Middle East ; Bacon, Francis ; Bamgboyé, Oladélé Ajiboyé ; Baumann, Andreas ; Baumgarten, Lothar ; Beaugrand, Catherine ; Beuys, Joseph ; Blank, Joachim ; Bonk, Ecke ; Brassaï ; Broodthaers, Marcel ; Bunting, Heath ; Burnett, Charles ; Bustamante, Jean-Marc ; Clark, Lygia ; Claus, Carlfriedrich ; Coleman, James ; Collective (La Ciutat de la Gent) ; Craig, Stephen ; Crandall, Jordan ; Douglas, Stan ; Dubuffet, Jean ; Evans, Walker ; Fahlström, Öyvind ; Farocki, Harun ; Fischli & Weiss ; Friedl, Peter ; Friese, Holger ; Gillick, Liam ; Gob Squad ; Goebbels, Heiner ; Golz, Dorothee ; Graham, Dan ; Grand, Toni ; Graumann, Hervé ; Grimonprez, Johan ; Grossarth, Ulrike ; Guston, Philip ; Haacke, Hans ; Hains, Raymond ; Hamilton, Richard ; Hapaska, Siobhán ; Hausswolff, Carl Michael von ; Heiman, Michal ; Henderson, Nigel ; Herold, Jörg ; Hesse, Eva ; Hill, Christine ; Hohenbüchler, Christine & Irene ; Honetschläger, Edgar ; Huber, Felix Stephan ; Höller, Carsten ; Ito, Toyo ; Jeron, Karl Heinz ; Jodi ; Kawara, On ; Kelley, Mike ; Kentridge, William ; Kippenberger, Martin ; Kleiner, Danielle Vallet ; Koester, Joachim ; Kogler, Peter ; Konrad, Aglaia ; Koolhaas, Rem ; Kroesinger, Hans-Werner ; Lafont, Suzanne ; Landau, Sigalit ; Lassnig, Maria ; Lauwers, Jan ; Le Corbusier ; Lerch, Antonia ; Levin, Mikael ; Levitt, Helen ; Marker, Chris ; Marshall, Kerry James ; Marthaler, Christoph ; Matta-Clark, Gordon ; Mau, Bruce ; McQueen, Steve ; Milev, Yana ; Mosler, Mariella ; Moulène, Jean-Luc ; Mucha, Reinhard ; Mullican, Matt ; Muntadas, Antoni ; Müller, Christian Philipp ; Ngui, Matthew ; Nicolai, Carsten ; etc.
boek
Keywords: David, Cathérine